If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x(3x + -9) + 2 = 0 Reorder the terms: 2x(-9 + 3x) + 2 = 0 (-9 * 2x + 3x * 2x) + 2 = 0 (-18x + 6x2) + 2 = 0 Reorder the terms: 2 + -18x + 6x2 = 0 Solving 2 + -18x + 6x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(1 + -9x + 3x2) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(1 + -9x + 3x2)' equal to zero and attempt to solve: Simplifying 1 + -9x + 3x2 = 0 Solving 1 + -9x + 3x2 = 0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. 0.3333333333 + -3x + x2 = 0 Move the constant term to the right: Add '-0.3333333333' to each side of the equation. 0.3333333333 + -3x + -0.3333333333 + x2 = 0 + -0.3333333333 Reorder the terms: 0.3333333333 + -0.3333333333 + -3x + x2 = 0 + -0.3333333333 Combine like terms: 0.3333333333 + -0.3333333333 = 0.0000000000 0.0000000000 + -3x + x2 = 0 + -0.3333333333 -3x + x2 = 0 + -0.3333333333 Combine like terms: 0 + -0.3333333333 = -0.3333333333 -3x + x2 = -0.3333333333 The x term is -3x. Take half its coefficient (-1.5). Square it (2.25) and add it to both sides. Add '2.25' to each side of the equation. -3x + 2.25 + x2 = -0.3333333333 + 2.25 Reorder the terms: 2.25 + -3x + x2 = -0.3333333333 + 2.25 Combine like terms: -0.3333333333 + 2.25 = 1.9166666667 2.25 + -3x + x2 = 1.9166666667 Factor a perfect square on the left side: (x + -1.5)(x + -1.5) = 1.9166666667 Calculate the square root of the right side: 1.38443731 Break this problem into two subproblems by setting (x + -1.5) equal to 1.38443731 and -1.38443731.Subproblem 1
x + -1.5 = 1.38443731 Simplifying x + -1.5 = 1.38443731 Reorder the terms: -1.5 + x = 1.38443731 Solving -1.5 + x = 1.38443731 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.5' to each side of the equation. -1.5 + 1.5 + x = 1.38443731 + 1.5 Combine like terms: -1.5 + 1.5 = 0.0 0.0 + x = 1.38443731 + 1.5 x = 1.38443731 + 1.5 Combine like terms: 1.38443731 + 1.5 = 2.88443731 x = 2.88443731 Simplifying x = 2.88443731Subproblem 2
x + -1.5 = -1.38443731 Simplifying x + -1.5 = -1.38443731 Reorder the terms: -1.5 + x = -1.38443731 Solving -1.5 + x = -1.38443731 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.5' to each side of the equation. -1.5 + 1.5 + x = -1.38443731 + 1.5 Combine like terms: -1.5 + 1.5 = 0.0 0.0 + x = -1.38443731 + 1.5 x = -1.38443731 + 1.5 Combine like terms: -1.38443731 + 1.5 = 0.11556269 x = 0.11556269 Simplifying x = 0.11556269Solution
The solution to the problem is based on the solutions from the subproblems. x = {2.88443731, 0.11556269}Solution
x = {2.88443731, 0.11556269}
| 1v/321v=2 | | 7x+3y=3x+5y | | -3(s+2)=0 | | -2(r+-1)=0 | | 41=19-2a | | b+30+2b= | | 5/8k=21/2 | | 50=16p+2 | | 8x-3=4x-21 | | 9a^2-18a+1=-4 | | 10=2(s+12) | | (3w^2-1)*w=96 | | (5/6)*x=10 | | W^2-2w=24+3w | | x^2-13=32 | | 24+9b=-3 | | 15-14=L | | 2(h+1)=10 | | 3(-8q+5)=4(q+1) | | -4+4x=-3x+24 | | 2n+9=33 | | 2(m+2)=8 | | -35=y-4 | | X+3=10-2X | | 1/2n-1/3=1 | | 2x+4y-9=0 | | F(X)=10X^2+27X-28 | | 10/3x=34/5 | | (X+2)(x-3)=2x(x-4) | | 4r^2-22r-42=0 | | 2X=3X-5+2X+12 | | x^2+4x+3=8x |